2021
DOI: 10.1002/advs.202003634
|View full text |Cite
|
Sign up to set email alerts
|

Parallel and Intertwining Threads of Domestication in Allopolyploid Cotton

Abstract: The two cultivated allopolyploid cottons, Gossypium hirsutum and Gossypium barbadense, represent a remarkable example of parallel independent domestication, both involving dramatic morphological transformations under selection from wild perennial plants to annualized row crops. Deep resequencing of 643 newly sampled accessions spanning the wild-to-domesticated continuum of both species, and their allopolyploid relatives, are combined with existing data to resolve species relationships and elucidate multiple as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 111 publications
6
72
0
Order By: Relevance
“…We observed similar divergence times between Gb-Gd (0.63 Mya; 95% CI: 0.37-1.26 Mya) and GhP-Gh (0.68 Mya; 95% CI: 0.41-1.14 Ma), con rming earlier data indicating that the Galapagos Island endemic G. darwinii (Gd), previously considered to be conspeci c with G. barbadense, diverged relatively recently from its mainland relative [40]. The genome sequences for the two species Ge and Gs complete the sampling of wild tetraploid Gossypium, and, as expected from prior analyses [10][11][12], they fall within the Gh-like clade, having all diverged from their most recent common ancestor around 0.75 Mya (95% CI, 0.42 -1.33 Mya) (Supplementary Fig. 5).…”
Section: Phylogenetic Analysis Of Tetraploid Gossypiumsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed similar divergence times between Gb-Gd (0.63 Mya; 95% CI: 0.37-1.26 Mya) and GhP-Gh (0.68 Mya; 95% CI: 0.41-1.14 Ma), con rming earlier data indicating that the Galapagos Island endemic G. darwinii (Gd), previously considered to be conspeci c with G. barbadense, diverged relatively recently from its mainland relative [40]. The genome sequences for the two species Ge and Gs complete the sampling of wild tetraploid Gossypium, and, as expected from prior analyses [10][11][12], they fall within the Gh-like clade, having all diverged from their most recent common ancestor around 0.75 Mya (95% CI, 0.42 -1.33 Mya) (Supplementary Fig. 5).…”
Section: Phylogenetic Analysis Of Tetraploid Gossypiumsupporting
confidence: 80%
“…Remarkably, an inversion event larger than 986.42 Kb on D01 was observed in both domesticated Gb and Gh (Fig. 3c), suggesting either a remarkable convergence under human selection, or more likely introgression between the two species, which has been common [12].…”
Section: Genomic Structural Variations (Svs)mentioning
confidence: 95%
See 1 more Smart Citation
“…We found that the At subgenome of all species contains 2-3% more nonsynonymous mutations that are inferred to be deleterious (Figure 3) even when only considering mutations that have arisen following the earliest allopolyploid diversification events, and correcting for removing the biases of unequal phylogenetic distances to each subgenome’s model progenitor diploid. Our work adds to a growing recognition that the two co-resident subgenomes in cotton allopolyploids may be shaped asymmetrically by evolutionary processes, including interspecific introgression and selection under domestication (Fang, Wang, et al 2017; Fang, Guan, et al 2017; Chen et al 2020; Yuan et al 2021), and that this phenomenon also extends to other important allopolyploid crop plants, including wheat (Pont and Salse 2017; Jiao et al 2018) and Brassica (Tong et al 2020) .…”
Section: Discussionmentioning
confidence: 77%
“…Included in our sampling was six polyploid species originating from a single polyploidization event 1-2 million years ago (Wendel 1989; Hu et al 2021), two diploid species representing models of the genome donors to the allopolyploids (A and D), and three species from Australia that served as outgroups for polarizing SNPs into ancestral and derived states. These sequences were previously described (Yuan et al 2021), and SRA codes for all 46 resequenced individuals are listed in Supplemental Table 1. For G. hirsutum , we randomly chose ten accessions that were classified in the “Wild” population from Yuan et al (Yuan et al 2021), and for the other species, we chose all accessions available that did not show evidence of being mislabeled, as determined by a PCA plot of the SNPs called.…”
Section: Methodsmentioning
confidence: 99%